2018
DOI: 10.1172/jci.insight.93626
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal β-oxidation regulates whole body metabolism, inflammatory vigor, and pathogenesis of nonalcoholic fatty liver disease

Abstract: Nonalcoholic fatty liver disease (NAFLD), a metabolic predisposition for development of hepatocellular carcinoma (HCC), represents a disease spectrum ranging from steatosis to steatohepatitis to cirrhosis. Acox1, a rate-limiting enzyme in peroxisomal fatty acid β-oxidation, regulates metabolism, spontaneous hepatic steatosis, and hepatocellular damage over time. However, it is unknown whether Acox1 modulates inflammation relevant to NAFLD pathogenesis or if Acox1-associated metabolic and inflammatory derangeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 60 publications
3
42
0
Order By: Relevance
“…We also assessed the expression of genes involved in fatty acid β-oxidation through qRT-PCR (Figure 10A). Carnitine palmitoyltransferase I and II (Cpt1a and Cpt2) are essential enzymes for β-oxidation of long chain fatty acid in mitochondria [39,40], while acyl-CoA oxidase 1 (Acox1) mediates fatty acid β-oxidation in peroxisome [39,41]. Cpt1a mRNA expression was significantly decreased in both Mkp-1 +/+ and Mkp-1 −/− mice upon E. coli infection, although expression levels in control conditions were similar in the two genotypes of mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also assessed the expression of genes involved in fatty acid β-oxidation through qRT-PCR (Figure 10A). Carnitine palmitoyltransferase I and II (Cpt1a and Cpt2) are essential enzymes for β-oxidation of long chain fatty acid in mitochondria [39,40], while acyl-CoA oxidase 1 (Acox1) mediates fatty acid β-oxidation in peroxisome [39,41]. Cpt1a mRNA expression was significantly decreased in both Mkp-1 +/+ and Mkp-1 −/− mice upon E. coli infection, although expression levels in control conditions were similar in the two genotypes of mice.…”
Section: Resultsmentioning
confidence: 99%
“…Fatty acids taken up from the blood can be converted in the liver to triglyceride by Dgat2 [56]. We think that the liver likely synthesizes triglyceride for consumption by other organs, because both the mitochondrial fatty acid β-oxidation-related Cpt1a protein [39,40]) and peroxisomal fatty acid β-oxidation protein Acox1 [39,41,57] are downregulated in Mkp-1 +/+ mice after E. coli infection (Figure 10). It is worth noting that a recent study has shown that p38 inhibition enhanced parenteral nutrition-induced hepatic steatosis and attenuated the expression of Cpt1a, Acox1, and Ppargc1a in a rat model [58].…”
Section: Discussionmentioning
confidence: 99%
“…The major mechanism driving hepatic TG accumulation is increased delivery of free fatty acids from peripheral adipose depots to the liver. Hepatic lipid disposal via mitochondrial/ peroxisomal β-oxidation and lipoprotein export are central mechanisms that function to eliminate potentially toxic free fatty acids 35,36,38 . To investigate why liver steatosis was ameliorated by GW7647 monotherapy and co-treatment, we assessed hepatic mitochondrial and peroxisomal β-oxidation-related gene expression of CPT1, 2, and ACOX1 by real-time PCR.…”
Section: Gw7647 Treatment Ameliorated Hf-cdaa Induced Liver Steatosismentioning
confidence: 99%
“…Analysis of mitochondrial function by Seahorse technology was performed as reported before with slight modifications (Gandhi et al, 2015; Moreno-Fernandez et al, 2018). Specifically, to assess baseline OCR, 10 5 Mϕ were plated in XF24 cell culture microplates (Seahorse Biosciences) and transfected with scramble or Mt3 siRNA for 5h in RPMI media as described above.…”
Section: Star ★ Methodsmentioning
confidence: 99%